Ransomware : ASEAN leaders should seize the momentum - Ponraj, Sithuraj (2022)
Increasing ransomware attacks have the potential to undermine daily lives by crippling critical infrastructure and disrupting essential services. ASEAN’s increasingly integrated digital economy makes it especially susceptible to fallout from such potential attacks. As ASEAN leaders meet in summit this week, they should take decisive measures to address the ransomware scourge.